Neo-Prophetism and the Contemporary Presidential Elections in Ghana - Washington, V. (University Of Ghana, 2018)
Over the last two decades, presidential and parliamentary elections in Ghana have been interspersed with prophecies mainly from the prophets of the neo-prophetic churches in Ghana. The neo-prophetic churches are one of the Pentecostal strand of churches in Ghana. These prophecies seeks or attempt to give an advance declaration of a presidential candidate whom God has chosen to win an impending presidential elections. This study, thus focuses on prophecies regarding presidential elections. The study captures and analyses some selected prophecies in both the 2012 and 2016 presidential elections in Ghana. The aim/objective has been to find or investigate whether or not prophecies affect the voting pattern of presidential elections in Ghana. In carrying out this objective, the study employs Georg Fohrer’s typology of prophecy in Ancient Israel. Methodologically, the study employed a phenomenological approach. The study also relied on both closed and open ended questionnaires to solicit the views of respondents on issues that remained central to this study. The study argued that current influence of political prophecies and the attempt of political parties or presidential candidate to solicit the help of prophets for electoral fortunes can be explained in the context of spiritual causality. That, in the broader context of abisa, aspirants to the Ghanaian presidency have the inclination to know their fortunes due to their belief in the supernatural and its causative factors. This study found out that though prophecies in general are believed and accepted by most Ghanaian Christians, political prophecies in the context of elections do not influence the voting pattern of the electorates. Rather, electorate concentrate on issues such as corruption, integrity of the leader or good leadership traits, party affiliations and other factors such as political party’s economic policies to vote during elections. The study recommends that in looking at the strife and tension during elections years in Ghana, prophets should exercise a caution and restraint regarding the manner and ways in which prophecies are given towards impending elections.
MPhil.
Keywords: Neo-Prophetism; Presidential Elections; Ghana